1996
DOI: 10.1002/j.1460-2075.1996.tb00969.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of calcium binding sites that regulate potentiation of a neuronal nicotinic acetylcholine receptor.

Abstract: The divalent cation calcium potentiates the physiological response of neuronal nicotinic receptors to agonists by enhancing ionic current amplitudes, apparent agonist affinity and cooperativity. Here we show that mutations in several consensus Ca2+ binding sequences from the N‐terminal domain of the neuronal alpha 7 nicotinic acetylcholine receptor alter Ca2+ potentiation of the alpha 7‐V201–5HT3 chimera. Mutations E18Q or E44Q abolish calcium‐enhanced agonist affinity but preserve the calcium increase of plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
155
2
4

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(172 citation statements)
references
References 47 publications
11
155
2
4
Order By: Relevance
“…1a). This chimeric receptor displayed the pharmacological properties, as well as the allosteric site for calcium potentiation (24), expected from its ␣7 nAChR ECD and was selective for chloride as expected from its GlyR ion channel. First, ACh-evoked current amplitudes increased in a dosedependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1a). This chimeric receptor displayed the pharmacological properties, as well as the allosteric site for calcium potentiation (24), expected from its ␣7 nAChR ECD and was selective for chloride as expected from its GlyR ion channel. First, ACh-evoked current amplitudes increased in a dosedependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The response of nAChRs is modulated by a variety of allosteric effectors (53). In particular, extracellular calcium potentiates several nAChRs both in vivo (54,55) and in transfected cells (56,57).…”
Section: Effect Of [Ca 2؉mentioning
confidence: 99%
“…Galzi et al (57) identified by site-directed mutagenesis in the chick ␣7 subunit two distinct consensus Ca 2ϩ -binding sequences involved in this potentiation. It was suggested that they would be located on two calmodulin-like EF-hands that would form Ca 2ϩ -binding sites.…”
Section: Effect Of [Ca 2؉mentioning
confidence: 99%
“…In native α7* receptors the modulation has been reported to be biphasic-with potentiation at sub-millimolar calcium concentrations and depression at higher concentrations (Bonfante-Cabarcas et al, 1996). The sequence determinants for this effect have been investigated for chick recombinant α7/5HT3 chimaeric receptors by Galzi et al (1996) who have identified residues α7 161-172 as particularly important: in the AChBP these residues are on the minus face, at the end of loop 9, which is near the extracellular end of the pore. Le Novère et al (2002) proposed, on the basis of their modelling of the α7 subunit on the AchBP, that the binding site for calcium is formed at the subunit interface by residues belonging to different subunits.…”
Section: Biophysical Properties Calciummentioning
confidence: 99%
“…Le Novère et al (2002) proposed, on the basis of their modelling of the α7 subunit on the AchBP, that the binding site for calcium is formed at the subunit interface by residues belonging to different subunits. These residues include some identified by Galzi et al (1996), such as E44 and E172, but also D43 and D41. Of these, E44 and D43 would be on the (+) side and E172 and D41 on the (-) side.…”
Section: Biophysical Properties Calciummentioning
confidence: 99%